PSMA PET Imaging in Glioblastoma: A Preclinical Evaluation and Theranostic Outlook - Kirchner, Maximilian A.; Holzgreve, Adrien; Brendel, Matthias; Orth, Michael; Ruf, Viktoria C.; Steiger, Katja; Pötter, Dennis; Gold, Lukas; Unterrainer, Marcus; Mittlmeier, Lena M.; Barci, Enio; Kälin, Roland E.; et al. (Frontiers in Oncology, 2021)
Background: Prostate specific membrane antigen (PSMA) PET imaging has recently gained attention in glioblastoma (GBM) patients as a potential theranostic target for PSMA radioligand therapy. However, PSMA PET has not yet been established in a murine GBM model. Our goal was to investigate the potential of PSMA PET imaging in the syngeneic GL261 GBM model and to give an outlook regarding the potential of PMSA radioligand therapy in this model. Methods: We performed an 18F-PSMA-1007 PET study in the orthotopic GL261 model (n=14 GBM, n=7 sham-operated mice) with imaging at day 4, 8, 11, 15, 18 and 22 post implantation. Time-activity-curves (TAC) were extracted from dynamic PET scans (0-120 min p. i.) in a subset of mice (n=4 GBM, n=3 sham-operated mice) to identify the optimal time frame for image analysis, and standardized-uptake-values (SUV) as well as tumor-to-background ratios (TBR) using contralateral normal brain as background were calculated in all mice. Additionally, computed tomography (CT), ex vivo and in vitro 18F-PSMA-1007 autoradiographies (ARG) were performed. Results: TAC analysis of GBM mice revealed a plateau of TBR values after 40 min p. i. Therefore, a 30 min time frame between 40-70 min p. i. was chosen for PET quantification. At day 15 and later, GBM mice showed a discernible PSMA PET signal on the inoculation site, with highest TBRmean in GBM mice at day 18 (7.3 ± 1.3 vs. 1.6 ± 0.3 in shams; p=0.024). Ex vivo ARG confirmed high tracer signal in GBM compared to healthy background (TBRmean 26.9 ± 10.5 vs. 1.6 ± 0.7 in shams at day 18/22 post implantation; p=0.002). However, absolute uptake values in the GL261 tumor remained low (e.g., SUVmean 0.21 ± 0.04 g/ml at day 18) resulting in low ratios compared to dose-relevant organs (e.g., mean tumor-to-kidney ratio 1.5E-2 ± 0.5E-2). Conclusions: Although 18F-PSMA-1007 PET imaging of GL261 tumor-bearing mice is feasible and resulted in high TBRs, absolute tumoral uptake values remained low and hint to limited applicability of the GL261 model for PSMA-directed therapy studies. Further investigations are warranted to identify suitable models for preclinical evaluation of PSMA-targeted theranostic approaches in GBM.